A Sociolegal Study of Trafficking in Women and Children in Indonesia - Trubus Rahardiansah Prawiraharja (Faculty of Law, Universitas Pekalongan, 2022)
This research aims to investigate the complex factors fuelling the crime of human trafficking in Indonesia, with a focus on trafficking in women and children. A sociolegal approach was used to understand the relationship between law and society in the context of human trafficking. Research methods, such as surveys, observations, and interviews, were tailored to the complexity of the study and the desired level of analysis. The findings show that human trafficking occurs due to economic, social, and cultural factors, with cases of sexual exploitation, labor, and contract marriage, especially in West Java and North Sumatra. The implication is that the central and local governments should pay attention to human security as a new concept from the national security perspective. Combating human trafficking needs to focus on the factors that make people vulnerable, with cross-border cooperation needed to prevent the movement of this crime before exploitation occurs. This research contributes to a further understanding of the dynamics of the crime of human trafficking. It provides a basis for further policy discussions to engage government, law enforcement officials, and communities in effective countermeasures.